2017
DOI: 10.1002/jppr.1345
|View full text |Cite
|
Sign up to set email alerts
|

Dispensing pattern for acute non‐infectious diarrhoea in children at community pharmacies in Thailand

Abstract: BackgroundIn cases of non‐infectious diarrhoea in children, the WHO and the Thai Antibiotic Smart Use (ASU) project recommend that no antibiotics should be given and drinking water should be replaced with oral rehydration salt (ORS) solution until the diarrhoea is finished. AimTo survey the dispensing pattern for non‐infectious diarrhoea treatment in children in Thailand. MethodsSimulated clients visited 91 Class I community pharmacies in five districts in Khon Kaen province and asked for advice to treat non‐i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
0
6
1
Order By: Relevance
“…Further, the majority of Sri Lankan pharmacy students reported that antibiotics consumption is appropriate for sore throat and diarrhoea in contrast to Australian students. This suggests a potential for antibiotic overuse, as the majority of diarrhoea illnesses do not require antibiotic therapy [ 36 ]. Similarly illnesses involving a sore throat do not usually require antibiotic therapy as it is most commonly a self-limiting viral illness [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, the majority of Sri Lankan pharmacy students reported that antibiotics consumption is appropriate for sore throat and diarrhoea in contrast to Australian students. This suggests a potential for antibiotic overuse, as the majority of diarrhoea illnesses do not require antibiotic therapy [ 36 ]. Similarly illnesses involving a sore throat do not usually require antibiotic therapy as it is most commonly a self-limiting viral illness [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Three articles conducted in Tanzania and Thailand [20][21][22] presented the percentage of antibiotic dispensing without a prescription related to class I, legally authorized to dispense antibiotics without prescription and class II that only sell them with a medical prescription. Two [20,22] of these articles presented the percentage related to the two pharmacy classes, while 1 article [21] only presented the percentage related to class I pharmacies. By comparing the percentages presented linked to both types of pharmacy, it is possible to verify that a higher percentage is related to the type II pharmacies in the two articles presented.…”
Section: Frequency Of Antibiotic Dispensation Without a Prescriptionmentioning
confidence: 99%
“…On the supply side, economic challenges and market competition, combined with widespread availability of cheap antibiotics and lack of adequate information on AMR, induced pharmacies to sell nonprescribed antibiotics. While some of these issues have been highlighted in previous work in Indonesia [18,33] and elsewhere in Asia [34][35][36][37][38], a key finding in our study is that policy reforms to improve access to affordable services and medicines may have unintended and undesirable effects on pharmacy practice and, ultimately, the control of AMR. Since the introduction of the JKN in 2014, a substantial increase in the utilisation of public health centres has been reported [39].…”
Section: Discussionmentioning
confidence: 74%